África – Bahia nas fotorreportagens de Verger, Freyre e Tavares em O Cruzeiro (1946-1960) - Oliveira, Karine Costa (2013)
This study aims to analyze images and representation widespread on Africa and on the African Bahia in the magazine O Cruzeiro. Therefore, we selected two sets of Photo Reports: Series consists of photographs of Pierre Verger and texts by Gilberto Freyre, entitled "turns that are Bahia" and the group Photo Reports produced in Bahia, but that reference a universe African constituted again photographs by Pierre Verger and texts Odorico Tavares. The temporal boundaries between 1946-1960 refer to the entry of Pierre Verger in that magazine as a photographer and focus that gave the elements of the African continent in its work. We take as a theoretical two notions: the shooting, according to Sontag, Kossoy and Muad, and the triad of Cultural History representation, practice ownership.